From foraging to farming in the Andes : new perspectives on food production and social organization - Dillehay, Tom D.; Kaulicke, Peter (Cambridge University Press, 2011)
"Archaeologists have always considered the beginnings of Andean civilization from ca. 13,000 to 6,000 years ago to be important in terms of the appearance of domesticated plants and animals, social differentiation, and a sedentary lifestyle, but there is more to this period than just these developments. During this time, the spread of crop production and other technologies, kinship-based labor projects, mound building, and population aggregation formed ever-changing conditions across the Andes. From Foraging to Farming in the Andes proposes a new and more complex model for understanding the transition from hunting and gathering to cultivation. It argues that such developments evolved regionally, were fluid and uneven, and were subject to reversal. This book develops these arguments from a large body of archaeological evidence, collected over thirty years in two valleys in northern Peru, and then places the valleys in the context of recent scholarship studying similar developments around world"--